PLANTS OF GANDHAMARDAN IN MATERNAL CARE: AN ETHNOBOTANICAL APPROACH - DAS, SONALIKA; MOHATY, SULAGANA; NAYAK, SHEETISWAPNA; BHATTA, KALPITA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The traditional use of plants in herbal medicine has paved the way for drug discovery. With a view of this, the present study was carried out in Gandhamardan hills which are a rich source of medicinal plants. However, there are copious reports about the plants used in maternal care. Therefore, an attempt has been made to record and document the plants of these hills utilized in maternal care. Methods: The ethnobotanical information on applications of different plant species to cure diseases and ailments of pregnancy, birth (parturition), and postpartum (puerperium) were documented through personal discussions, interviews with focused groups combined with field visits, voice recordings, and photo documentation. Results: The study showed that 24 vascular plant species belonging to 24 genera and 22 families have been used in maternal care. Most of the species were herbs (50%) followed by trees (32.5%), climbers, and herbs (20%). It was observed that among all the parts, generally leaves were widely used. Conclusion: This ethnobotanical study documented the use of plants among the local community. It also revealed that the medicinal plants of the hills are a cheap source of herbal drugs for the rural communities. The information gathered can be used for further scientific investigation to develop new plant-based commercial drugs as they will be safer than synthetic drugs.